Uveljavljanje formativnega ocenjevanja v visokošolskem izobraževanju - Šteh, Barbara (Psihološka obzorja (Ljubljana), 2020)
Formative assessment has been generally acknowledged at all levels of education, including higher education. However, the empirical data on its use and effectiveness in higher education is scarce and inconclusive. The issue is an ambiguous understanding of formative assessment. Therefore, the main aim of this article is to contribute to the clarification of this concept by analysing its key characteristics. Formative assessment has to be embedded in the entire teaching and learning process. In this paper we focus on effectiveness of formative assessment and factors that influence its implementation in higher education. Teachers in higher education have an essential role in creating learning environments that enable quality formative assessment. This includes forming suitable tasks and challenges for students, giving them relevant feedback, as well as receiving, understanding and responding to the feedback from students themselves. Effective formative assessment empowers students to ask reflexive questions, evaluate the quality of their knowledge, and regulate their learning. Finally, we draw attention to the entire context as an important condition for implementation of formative assessment in higher education. The context includes the culture of an institution, the demands of an educationalprogramme, general assessment methods, and especially the qualifications of higher education teachers for accomplishing quality assessment. We proposed several key guidelines for establishing the conditions under which assessment can support students' learning.
Keywords: college students; educational psychology; feedback; formative assessment; formativno ocenjevanje; higher education; higher education teachers; pedagoška psihologija; povratna informacija; samoregulacijsko učenje; samouravnavanje učenja; self-regulated learning; študenti; visokošolska pedagogika; visokošolski učitelji; visokošolsko izobraževanje